Information technology security - Selamat, Siti Rahayu; Yusof, Robiah; Abdollah, Mohd Faizal; Bahaman, Nazrulazhar (Pearson-Prentice Hall, 2006)
The objective of this book is to introduce student in preparing a secure computing environment in theory and practical by using secure software, hardware and network. The task in the lab project will involve the managing setup process, PGP application, preventive tools, anti-virus and other security tools. These tools will help student in understanding and applying the computer and information security areas and processes. Each lab project offers student many opportunities to get hands-on and build new security tools skills. It also exposes students about threats that always attack their computing environment such as their information and network.